BUKTI INDEPENDENSI DAN KOMPETENSI AUDITOR TERHADAP KUALITAS AUDIT KAP DI KOTA SURABAYA: Etika Auditor Pemoderasi - Murdiansyah, Isnan; Lestari, Yona Octiani (LP2M Institut Teknologi dan Bisnis Asia Malang, 2023)
The purpose of this study was to obtain empirical evidence of audit fees moderating the effect of auditor independence and auditor competence on audit quality with audit fees as moderating. The dependent variable in this study is audit quality, the independent variable in this study is the independence and competence of auditors, and the moderating variable in this study is the audit fee. The research was conducted at a Public Accounting Firm (KAP) in the city of Surabaya which is registered with the Indonesian Institute of Certified Public Accountants (IAPI) in 2022. This type of research is quantitative. The data in this study used primary data by distributing questionnaires. The sampling method used convenience sampling, which is a technique for selecting samples based on the number of people in the Public Accounting Firm. The data analysis technique used is Moderated Regression Analysis (MRA). The results of this study indicate that there is a significant positive effect of audit fees that moderate auditor independence and auditor competence on audit quality. The results of this study are expected to assist auditors in knowing the effect of improving audit quality in Public Accounting Firms.